A spherical starch-based cement-based material internal curing agent and a synthesis method thereof

By synthesizing spherical starch-based hyperwater absorption polymer (SSSP) using reverse phase suspension method, the existing petroleum-based SAP has been solved, and the problem of poor salt resistance and irregular particles in cement-based materials is achieved, achieving efficient self-shrinkage of cement slurry.

CN118290655BActive Publication Date: 2025-03-28HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410401589.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-03-28
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

The petroleum-based hyperwater-absorbent polymers (SAPs) used in existing cement-based materials have problems of poor salt resistance and irregular particles, which affects their performance in complex environments.

Method used

By selecting starch as the raw material, spherical starch-based hyperwater absorption polymer (SSSP) is synthesized by reverse phase suspension method to improve its spherical shape and water absorption properties.

Benefits of technology

The prepared spherical starch-based SAP (SSSP) has high spherical shape, good water absorption and water retention rate, which can effectively slow down the self-shrinkage of cement slurry and meet the requirements of internal maintenance of cement-based materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118290655B_ABST
    Figure CN118290655B_ABST
Patent Text Reader

Abstract

A spherical starch-based cement-based material internal curing agent and a synthesis method thereof, belonging to the technical field of cement-based material internal curing agent preparation. It is to prepare a regular-shaped cement-based material internal curing agent. The present invention comprises the following steps: preparing an aqueous phase solution, including a gelatinized starch solution, an initiator solution and a monomer solution; preparing an oil phase solution under the protection of nitrogen to form a suspended dispersion system; slowly adding the prepared gelatinized starch solution and initiator solution to the prepared oil phase solution under the protection of nitrogen and stirring conditions, stirring for a certain period of time and then adding the monomer solution dropwise, and performing a polymerization reaction under stirring conditions for a certain period of time after the dropwise addition is completed, and then cooling to room temperature under stirring conditions, standing to obtain a mixture, centrifuging it, pouring it into anhydrous ethanol stirred at a high speed, washing it for a certain period of time, and then drying it in a vacuum drying oven to obtain a spherical starch-based cement-based material internal curing agent. The particles prepared by the present invention have a significant spherical shape and a uniform particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of cement-based material internal curing agent, and specifically relates to a spherical starch-based cement-based material internal curing agent and a synthesis method thereof. Background Art

[0002] Super absorbent polymer (SAP) is a water-insoluble polymer material that swells in water and retains most of the water in its structure. Since the U.S. Department of Agriculture introduced the first super absorbent resin in the 1970s, SAP has broad application prospects in various fields. Most SAPs are synthesized using petroleum products as raw materials, among which acrylic acid and its salts and acrylamide are widely used as monomers. Representative products include sodium polyacrylate (PAA) and acrylic acid-acrylamide copolymer (PAM). There are also some bio-based SAPs synthesized by grafting copolymerization using natural polymers such as alginate and chitosan, and have been initially applied in agriculture, forestry, horticulture, and medicine and health. However, most of the above SAPs are formed by intramolecular polymerization through aqueous solution polymerization, and the products are irregular particles. When irregular SAPs are applied to cement-based materials, problems such as particle aggregation, slow water absorption, and volume instability usually occur.

[0003] Spherical SAP particles have uniform size and large specific surface area, and can be evenly dispersed and quickly absorb water when used. The current synthesis of spherical SAP mainly uses petroleum-based products acrylic acid (AA) and acrylamide (AM) for cross-linking copolymerization, which mainly has the disadvantages of high cost, poor biodegradability, low water absorption and poor salt resistance. Starch is a renewable and biodegradable polysaccharide polymer that can be extracted from various plant sources. It is abundant in source and low in cost. Starch has abundant hydroxyl groups, which is conducive to providing grafting points for hydrophilic groups. At present, there are many studies on the synthesis of SAP by grafting propylene monomers with starch, but most of the products are mainly irregular particles synthesized by aqueous solution polymerization. When SAP is introduced into concrete, irregular particles have some disadvantages, such as affecting mechanical properties and poor durability. Summary of the invention

[0004] The problem to be solved by the present invention is to prepare a spherical cement-based material internal curing agent, and a spherical starch-based cement-based material internal curing agent and a synthesis method thereof are provided.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions:

[0006] A method for synthesizing a spherical starch-based cement-based material internal curing agent comprises the following steps:

[0007] S1. configuring an aqueous solution, including a gelatinized starch solution, an initiator solution and a monomer solution;

[0008] S2. Under the protection of nitrogen, an oil phase solution is prepared to form a suspended dispersion system;

[0009] S3. Under the protection of nitrogen and under stirring conditions, the gelatinized starch solution and the initiator solution prepared in step S1 are slowly added to the oil phase solution prepared in step S2, and the monomer solution is added dropwise after stirring for a certain period of time. After the addition is completed, the polymerization reaction is carried out under stirring conditions for a certain period of time, and then cooled to room temperature under stirring conditions, and the mixture is allowed to stand to obtain;

[0010] S4. The bottom white emulsion in the mixture obtained in step S3 is centrifuged to obtain a high-purity emulsion;

[0011] S5. The high-purity emulsion obtained in step S4 is slowly poured into anhydrous ethanol stirred at high speed, washed several times, and then dried in a vacuum drying oven to obtain a spherical starch-based cement-based material curing agent;

[0012] S6. Take a SEM photograph of the spherical starch-based cement-based material internal curing agent obtained in step S5, and use image processing method to calculate the particle sphericity of the obtained SEM photograph. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. Particles with a sphericity greater than or equal to 0.9 are regarded as a spherical starch-based cement-based material internal curing agent.

[0013] Furthermore, the specific implementation method of step S1 includes the following steps:

[0014] S1.1. Prepare a gelatinized starch solution: Weigh starch and deionized water in a mass ratio of 1:15-1:20, then place the starch in a three-necked flask, add deionized water, and gelatinize for 0.5-1.5h at a stirring rate of 200r / min-250r / min in a water bath at 85℃-90℃ under nitrogen protection to obtain a gelatinized starch solution;

[0015] S1.2. According to the weighed starch mass in step S1.1, the hydrophilic monomer, initiator and cross-linking agent are weighed respectively. The mass ratio of starch to hydrophilic monomer is 1:4.5-1:6, the initiator is 1wt%-1.5wt% of the mass of the hydrophilic monomer, and the cross-linking agent is 0.08wt%-0.12wt% of the mass of the hydrophilic monomer;

[0016] S1.3. Prepare initiator solution: weigh initiator and deionized water in a mass ratio of 1:5-1:10, stir evenly under nitrogen to obtain an initiator solution;

[0017] S1.4. Prepare the monomer solution: weigh the hydrophilic monomer and deionized water in a mass ratio of 1:5-1:10, stir evenly under nitrogen protection, add the cross-linking agent, and stir evenly to obtain a monomer solution.

[0018] Furthermore, in step S1, the starch is one of cassava starch and corn starch, the hydrophilic monomer is an amide compound carrying an amide group and a sulfonic acid compound carrying a sulfonic acid group, the initiator is one or a combination of two of sodium persulfate and mercaptosuccinate, and the crosslinking agent is divinylphenol or ethylenediamine.

[0019] Further, the amide compound carrying an amide group is one or a combination of methacrylamide and dimethylacrylamide, and the sulfonic acid compound carrying a sulfonic acid group is one or a combination of sulfonic methacrylate and sulfonic acrylate;

[0020] Furthermore, in step S2, the oil phase solvent and the dispersant are weighed in a mass ratio of 100:3.5-100:5.5, added into a four-necked flask, mixed and stirred for 30 minutes at 25°C-30°C under N2 protection to form a stable suspension dispersion system to obtain an oil phase solution.

[0021] Furthermore, the oil phase solvent in step S3 is one of cyclohexane, n-heptane or n-hexadecane, and the dispersant is one of Span-80 and Tween-80 sodium dodecyl sulfate or a combination of the two.

[0022] Furthermore, in step S3, the volume ratio of the oil phase solution to the water phase solution is 2.5:1-4.5:1, the polymerization reaction temperature is 65°C-85°C, the stirring speed during the polymerization reaction is 350r / min-500r / min, the polymerization reaction time is 2.5h-3h, and the standing time is 5min-10min.

[0023] Furthermore, in step S5, the ethanol washing times are 3 times, and the product is placed in a vacuum drying oven and dried at 45° C. for 24 hours.

[0024] Furthermore, the specific implementation method of step S6 includes the following steps:

[0025] S6.1. Take a SEM photograph of a spherical starch-based cement-based material curing agent obtained in step S5;

[0026] S6.2. Process the SEM photograph obtained in step S6.1 into a binary image, extract the projected area of ​​the particles of the spherical starch-based cement-based material curing agent and the diameter of the minimum circumscribed circle of the particles;

[0027] S6.3. Set the sphericity s to the ratio of the diameter D of the circle with equal projected area of ​​the particle to the diameter Dc of the smallest circumscribed circle of the particle. The sphericity value range is 0-1. The closer s is to 1, the closer the shape of the particle is to a sphere. The calculation expression is:

[0028]

[0029]

[0030] Where S is the projected area of ​​the particle;

[0031] S6.4. Compare the sphericity s obtained in step S6.3. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, a spherical starch-based cement-based material internal curing agent is obtained.

[0032] A spherical starch-based cement-based material internal curing agent is realized based on the synthesis method of the spherical starch-based cement-based material internal curing agent and is synthesized based on a reverse suspension method.

[0033] Beneficial effects of the present invention:

[0034] The synthesis method of a spherical starch-based cement-based material internal curing agent described in the present invention is aimed at the shortcomings of poor salt resistance of traditional petroleum-based SAP and irregular particles of bio-based SAP in the complex environment of cement-based materials. Starch is selected as a raw material, and the spherical starch-based cement-based material internal curing agent (SSSP) is synthesized by an inverse suspension method. With the goal of improving the sphericity, the SSSP synthesis process is quantitatively characterized and optimized, its water absorption performance is tested and microscopically characterized, and finally it is used as an internal curing agent and added to cement paste, which has a good effect on slowing down the self-shrinkage of cement paste.

[0035] The synthesis method of a spherical starch-based cement-based material internal curing agent described in the present invention uses the reverse suspension method, selects different combinations of hydrophilic groups and single factor tests, and successfully prepares a spherical starch-based highly absorbent polymer-SSSP. Its optimal water absorption rate is 1320g / g (deionized water) in deionized water and 145g / g (cement filtrate) in cement filtrate. It has a high water retention rate, a continuous water absorption process, and a sphericity of 0.95. The microscopic characterization results also show that the starch molecular structure is destroyed, the hydrophilic groups are successfully grafted, and the prepared SSSP particles are significantly spherical and have uniform particle sizes. After being added to cement slurry, it can effectively slow down the self-shrinkage of cement slurry by 76.2%, which can meet the requirements of internal curing of cement-based materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a flow chart of a method for synthesizing a spherical starch-based cement-based material internal curing agent according to the present invention;

[0037] Figure 2 This is an example of a SEM photo of a spherical starch-based cement-based material internal curing agent according to the present invention;

[0038] Figure 3 This is an example of a binary image of a spherical starch-based cement-based material internal curing agent according to the present invention;

[0039] Figure 4 This is a bar graph comparing the water absorption of SSSP according to the method of the first embodiment of the present invention;

[0040] Figure 5 It is a bar graph comparing the water retention rate of SSSP according to the method of the first specific embodiment of the present invention;

[0041] Figure 6 The water release time curve of the SSSP gel of the method of the first specific embodiment of the present invention;

[0042] Figure 7 This is a comparative curve of FT-IR analysis of a spherical starch-based cement-based material internal curing agent prepared by the method of the second specific embodiment of the present invention;

[0043] Figure 8 This is a SEM photo of SSSP particles of a spherical starch-based cement-based material internal curing agent prepared by the method of the second specific embodiment of the present invention;

[0044] Fig. 9 This is a SEM photo of SSSP particles of a spherical starch-based cement-based material internal curing agent prepared by the method of the third specific embodiment of the present invention;

[0045] Fig.10 This is a photo of SSSP particles of a spherical starch-based cement-based material internal curing agent prepared by the third method of the specific embodiment of the present invention after absorbing water;

[0046] Fig.11 This is a photo of SSSP particles of a spherical starch-based cement-based material internal curing agent prepared by the fourth method of the specific embodiment of the present invention after absorbing water;

[0047] Fig.12 This is a comparison curve of the effect of SSSP, a spherical starch-based cement-based material internal curing agent prepared by the fourth method of the specific embodiment of the present invention, on the autogenous shrinkage of cement paste. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the specific embodiments described are only part of the embodiments of the present invention, rather than all of the specific embodiments. The components of the specific embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations, and the present invention can also have other embodiments.

[0049] Therefore, the following detailed description of the specific embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected specific embodiments of the present invention. Based on the specific embodiments of the present invention, all other specific embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0050] In order to further understand the content, features and effects of the present invention, the following specific implementation methods are given as examples, and the attached Figure 1 -Attached Fig.12 The detailed instructions are as follows: Specific implementation method one:

[0052] A method for synthesizing a spherical starch-based cement-based material internal curing agent comprises the following steps:

[0053] S1. configuring an aqueous solution, including a gelatinized starch solution, an initiator solution and a monomer solution;

[0054] Furthermore, the specific implementation method of step S1 includes the following steps:

[0055] S1.1. Prepare a gelatinized starch solution: Weigh starch and deionized water in a mass ratio of 1:15-1:20, then place the starch in a three-necked flask, add deionized water, and gelatinize for 0.5-1.5h at a stirring rate of 200r / min-250r / min in a water bath at 85℃-90℃ under nitrogen protection to obtain a gelatinized starch solution;

[0056] S1.2. According to the weighed starch mass in step S1.1, the hydrophilic monomer, initiator and cross-linking agent are weighed respectively. The mass ratio of starch to hydrophilic monomer is 1:4.5-1:6, the initiator is 1wt%-1.5wt% of the mass of the hydrophilic monomer, and the cross-linking agent is 0.08wt%-0.12wt% of the mass of the hydrophilic monomer;

[0057] S1.3. Prepare initiator solution: weigh initiator and deionized water in a mass ratio of 1:5-1:10, stir evenly under nitrogen to obtain an initiator solution;

[0058] S1.4. Prepare a monomer solution: Weigh the hydrophilic monomer and deionized water in a mass ratio of 1:5-1:10, stir evenly under nitrogen, adjust the pH value with sodium hydroxide, then add the crosslinking agent, stir evenly, and obtain a monomer solution;

[0059] Furthermore, in step S1, the starch is one of cassava starch and corn starch, the hydrophilic monomer is an amide compound carrying an amide group and a sulfonic acid compound carrying a sulfonic acid group, the initiator is one or a combination of two of sodium persulfate and mercaptosuccinate, and the crosslinking agent is divinylphenol or ethylenediamine;

[0060] Further, the amide compound carrying an amide group is one or a combination of methacrylamide and dimethylacrylamide, and the sulfonic acid compound carrying a sulfonic acid group is one or a combination of sulfonic methacrylate and sulfonic acrylate;

[0061] S2. Under the protection of nitrogen, an oil phase solution is prepared to form a suspended dispersion system;

[0062] Further, in step S2, the oil phase solvent and the dispersant are weighed in a mass ratio of 100:3.5-100:5.5, added into a four-necked flask, mixed and stirred for 30 minutes at 25° C.-30° C. under N2 protection to form a stable suspension dispersion system, and obtain an oil phase solution;

[0063] S3. Under the protection of nitrogen and under stirring conditions, the gelatinized starch solution and the initiator solution prepared in step S1 are slowly added to the oil phase solution prepared in step S2, and the monomer solution is added dropwise after stirring for a certain period of time. After the addition is completed, the polymerization reaction is carried out under stirring conditions for a certain period of time, and then cooled to room temperature under stirring conditions, and the mixture is allowed to stand to obtain;

[0064] Further, the oil phase solvent in step S3 is one of cyclohexane, n-heptane or n-hexadecane, and the dispersant is one of Span-80 and Tween-80 sodium dodecyl sulfate or a combination thereof;

[0065] Furthermore, in step S3, the volume ratio of the oil phase solution to the water phase solution is 2.5:1-4.5:1, the polymerization temperature is 65°C-85°C, the stirring speed during the polymerization is 350r / min-500r / min, the polymerization time is 2.5h-3h, and the standing time is 5min-10min;

[0066] S4. The bottom white emulsion in the mixture obtained in step S3 is centrifuged to obtain a high-purity emulsion;

[0067] S5. The high-purity emulsion obtained in step S4 is slowly poured into anhydrous ethanol stirred at high speed, washed several times, and then dried in a vacuum drying oven to obtain a spherical starch-based cement-based material curing agent;

[0068] Furthermore, in step S5, the ethanol washing times are 3 times, and the drying condition in a vacuum drying oven is 45° C. for 24 hours;

[0069] S6. Take a SEM photo of the spherical starch-based cement-based material internal curing agent obtained in step S5, and use an image processing method to calculate the particle sphericity of the obtained SEM photo. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, the sphericity is a spherical starch-based cement-based material internal curing agent.

[0070] Furthermore, the specific implementation method of step S6 includes the following steps:

[0071] S6.1. Take a SEM photograph of a spherical starch-based cement-based material curing agent obtained in step S5;

[0072] S6.2. Process the SEM photograph obtained in step S6.1 into a binary image, extract the projected area of ​​the particles of the spherical starch-based cement-based material curing agent and the diameter of the minimum circumscribed circle of the particles;

[0073] S6.3. Set the sphericity s to the ratio of the diameter D of the circle with equal projected area of ​​the particle to the diameter Dc of the smallest circumscribed circle of the particle. The sphericity value range is 0-1. The closer s is to 1, the closer the shape of the particle is to a sphere. The calculation expression is:

[0074]

[0075]

[0076] Where S is the projected area of ​​the particle;

[0077] S6.4. Compare the sphericity s obtained in step S6.3. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, a spherical starch-based cement-based material internal curing agent is obtained.

[0078] The method for synthesizing a spherical starch-based cement-based material curing agent described in this embodiment uses an image processing method to calculate the sphericity of the particles. The specific process is as follows: a certain number of SEM images (RGB format) of SAP particles are taken and processed into binary image photos by a written image processing program. Figure 2 and Figure 3 As shown, if the synthesized spherical particles satisfy the sphericity of 0.9 or above, they can be regarded as basically spherical particles and the preparation is successful. If the sphericity of the particles does not meet this requirement, the preparation process needs to be adjusted accordingly.

[0079] The tea bag method is used to determine the water absorption rate of SAP in the spherical starch-based cement-based material curing agent prepared by the synthesis method of the spherical starch-based cement-based material curing agent described in this embodiment. SAP is first vacuum dried for 24 hours (m0), and the particle size is 0.25-0.5mm. Subsequently, SAP is placed in a moistened tea bag (m1) and a beaker, and 200mL of solution is added. After the solution has been absorbed for 12 hours, remove the tea bag, wipe the surface of the tea bag dry (m), and the water absorption rate is calculated as (m-m1-m0) / m0. The solution absorbed for 12 hours (m 2 ) of SAP were packed in tea bags, placed in CF for 6 h, and weighed (m 3 The water storage capacity calculation formula is (m 3 / m 2 )×100%. The SAP that has absorbed water for 12 hours is placed in an evaporating dish (temperature: 20±5°C, humidity: 40±5%). The water absorption rate at different times is calculated as the water release rate of SAP.

[0080] The test solutions used were as follows:

[0081] Deionized water, DW, with a pH of 7.2;

[0082] tap water, TW;

[0083] Saline solution, SCS, 0.9% sodium chloride solution by mass;

[0084] Cement slurry filtrate, CSF, cement filtrate obtained by filtration with a water-cement ratio (w / c) of 10;

[0085] The test results obtained are as follows Figure 4 , Figure 5 and Figure 6 As shown:

[0086] from Figure 4 It can be seen that as the number of ions in the solution increases, the water absorption rate of SSSP gradually decreases. DW is very different from CSF because the latter has the highest number and type of ions. The water absorption of SSSP is a process of gradual expansion of its internal network structure. According to Flory's water absorption formula, the increase in the ion osmotic pressure in the solution will reduce the water absorption rate of SAP. Strongly hydrophilic -SO3H and non-ionic -CONH2 are introduced into SSSP, thus ensuring salt resistance while increasing the water absorption rate.

[0087] from Figure 5It can be seen that with the increase in the type and number of ions in the solution, the water storage rate of SSSP gel gradually increases, which is related to its initial water absorption rate. In deionized water, SSSP relies on the network structure to wrap a large amount of water, which is a physical adsorption process. After being affected by the outside world, a large amount of water will be released, so the water storage rate is reduced. The ions in CSF will produce common ion effects and complex reactions with SSSP, and store water in a chemically combined manner, so the water storage rate is higher. The water storage performance of SAP gel under physical action will affect its internal curing effect in cement-based materials.

[0088] Figure 6 The changes in the water release process of SSSP gel within one week are shown. The water absorption rate of SSSP decreases with time, and the water release rate of SSSP is related to its initial water absorption rate. After swelling in CSF, SSSP completes the water release process in 108h. During the water release process of SSSP, the hydrophilic groups are gradually protonated, and hydrogen bonds are formed between adjacent groups, causing the network structure to shrink and drain outward until the humidity gradient between the SSSP structure and the environment is zero. Specific implementation method 2:

[0090] A method for synthesizing a spherical starch-based cement-based material internal curing agent comprises the following steps:

[0091] S1. configuring an aqueous solution, including a gelatinized starch solution, an initiator solution and a monomer solution;

[0092] Furthermore, the specific implementation method of step S1 includes the following steps:

[0093] S1.1. Prepare gelatinized starch solution: Weigh starch and deionized water in a mass ratio of 1:15, then place the starch in a three-necked flask, add deionized water, and gelatinize for 0.5 h at a stirring rate of 200 r / min in a water bath at 85°C under nitrogen protection to obtain a gelatinized starch solution;

[0094] S1.2. According to the weighed starch mass in step S1.1, the hydrophilic monomer, initiator, and cross-linking agent are weighed respectively. The mass ratio of starch to hydrophilic monomer is 1:4.5, the initiator is 1wt% of the mass of the hydrophilic monomer, and the cross-linking agent is 0.08wt% of the mass of the hydrophilic monomer;

[0095] S1.3. Prepare initiator solution: weigh initiator and deionized water in a mass ratio of 1:5, stir evenly under nitrogen protection to obtain an initiator solution;

[0096] S1.4. Prepare a monomer solution: weigh a hydrophilic monomer and deionized water in a mass ratio of 1:5, stir evenly under nitrogen protection, adjust the pH value with sodium hydroxide, then add a crosslinking agent, stir evenly, and obtain a monomer solution;

[0097] Furthermore, in step S1, the starch is cassava starch, the hydrophilic monomer is an amide compound carrying an amide group and a sulfonic acid compound carrying a sulfonic acid group, the initiator is mercaptosuccinate, and the crosslinking agent is divinylphenol;

[0098] Further, the amide compound carrying an amide group is a composition of methacrylamide and dimethylacrylamide in a mass ratio of 1:1, and the sulfonic acid compound carrying a sulfonic acid group is a composition of sulfonic methacrylate and sulfonic acrylate in a mass ratio of 1:1;

[0099] S2. Under the protection of nitrogen, an oil phase solution is prepared to form a suspended dispersion system;

[0100] Furthermore, in step S2, the oil phase solvent and the dispersant are weighed in a mass ratio of 100:5, added into a four-necked flask, mixed and stirred for 30 minutes at 30° C. under N2 protection to form a stable suspension dispersion system, and obtain an oil phase solution;

[0101] S3. Under the protection of nitrogen and under stirring conditions, the gelatinized starch solution and the initiator solution prepared in step S1 are slowly added to the oil phase solution prepared in step S2, and the monomer solution is added dropwise after stirring for a certain period of time. After the addition is completed, the polymerization reaction is carried out under stirring conditions for a certain period of time, and then cooled to room temperature under stirring conditions, and the mixture is allowed to stand to obtain;

[0102] Furthermore, the oil phase solvent in step S3 is cyclohexane, and the dispersant is a composition of Span-80 and Tween-80 in a mass ratio of 1:3;

[0103] Furthermore, in step S3, the volume ratio of the oil phase solution to the water phase solution is 3:1, the polymerization temperature is 65° C., the stirring speed during the polymerization is 450 r / min, the polymerization time is 2.5 h, and the standing time is 5 min;

[0104] S4. The bottom white emulsion in the mixture obtained in step S3 is centrifuged to obtain a high-purity emulsion;

[0105] S5. The high-purity emulsion obtained in step S4 is slowly poured into anhydrous ethanol stirred at high speed, washed several times, and then dried in a vacuum drying oven to obtain a spherical starch-based cement-based material curing agent;

[0106] Furthermore, in step S5, the ethanol washing times are 3 times, and the drying condition in a vacuum drying oven is 45° C. for 24 hours;

[0107] S6. Take a SEM photo of the spherical starch-based cement-based material internal curing agent obtained in step S5, and use an image processing method to calculate the particle sphericity of the obtained SEM photo. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, the sphericity is a spherical starch-based cement-based material internal curing agent.

[0108] Furthermore, the specific implementation method of step S6 includes the following steps:

[0109] S6.1. Take a SEM photograph of a spherical starch-based cement-based material curing agent obtained in step S5;

[0110] S6.2. Process the SEM photograph obtained in step S6.1 into a binary image, extract the projected area of ​​the particles of the spherical starch-based cement-based material curing agent and the diameter of the minimum circumscribed circle of the particles;

[0111] S6.3. Set the sphericity s to the ratio of the diameter D of the circle with equal projected area of ​​the particle to the diameter Dc of the smallest circumscribed circle of the particle. The sphericity value range is 0-1. The closer s is to 1, the closer the shape of the particle is to a sphere. The calculation expression is:

[0112]

[0113]

[0114] Where S is the projected area of ​​the particle;

[0115] S6.4. Compare the sphericity s obtained in step S6.3. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, a spherical starch-based cement-based material internal curing agent is obtained.

[0116] The method for synthesizing a spherical starch-based cement-based material internal curing agent described in this embodiment, the synthesized spherical starch-based cement-based material internal curing agent is subjected to FT-IR analysis as follows Figure 7 As shown, Figure 7 Medium 2940cm -1 and 1560cm -1 The peaks at 1660cm represent the two molecular structures of starch, namely the characteristic vibrations of CH and OH. -1 and 1290cm -1 The peak at 1210 cm is the characteristic vibration of -CONH2 group. -1 and 1060cm -1The peak at is the -SO3H group. The characteristic peaks of -SO3H and -CONH2 were found in SSSP. The significant changes before and after chemical modification indicate that the hydrophilic group has been successfully grafted to the starch backbone, indicating that after the synthesis of SSSP, the molecular structure of starch has changed significantly, and there are also interactions within the molecular structure.

[0117] The method for synthesizing a spherical starch-based cement-based material internal curing agent described in this embodiment, the SEM photo of the synthesized spherical starch-based cement-based material internal curing agent is as follows Figure 8 As shown, the particle size distribution of SSSP particles is uniform and the particle surface is smooth. Specific implementation method three:

[0119] A method for synthesizing a spherical starch-based cement-based material internal curing agent comprises the following steps:

[0120] S1. configuring an aqueous solution, including a gelatinized starch solution, an initiator solution and a monomer solution;

[0121] Furthermore, the specific implementation method of step S1 includes the following steps:

[0122] S1.1. Prepare gelatinized starch solution: Weigh starch and deionized water in a mass ratio of 1:20, then place the starch in a three-necked flask, add deionized water, and gelatinize at a stirring rate of 200 r / min at 85°C in a water bath under nitrogen protection for 0.5-1.5h to obtain a gelatinized starch solution;

[0123] S1.2. According to the weighed starch mass in step S1.1, the hydrophilic monomer, initiator, and cross-linking agent are weighed respectively. The mass ratio of starch to hydrophilic monomer is 1:6, the initiator is 1.5wt% of the mass of the hydrophilic monomer, and the cross-linking agent is 0.12wt% of the mass of the hydrophilic monomer;

[0124] S1.3. Prepare initiator solution: weigh initiator and deionized water in a mass ratio of 1:10, stir evenly under nitrogen protection to obtain an initiator solution;

[0125] S1.4. Prepare a monomer solution: weigh a hydrophilic monomer and deionized water in a mass ratio of 1:10, stir evenly under nitrogen, adjust the pH value with sodium hydroxide, then add a crosslinking agent, stir evenly, and obtain a monomer solution;

[0126] Furthermore, in step S1, the starch is corn starch, the hydrophilic monomer is an amide compound carrying an amide group and a sulfonic acid compound carrying a sulfonic acid group, the initiator is sodium persulfate, and the cross-linking agent is ethylenediamine;

[0127] Further, the amide compound carrying an amide group is methacrylamide, and the sulfonic acid compound carrying a sulfonic acid group is sulfonic methacrylate;

[0128] S2. Under the protection of nitrogen, an oil phase solution is prepared to form a suspended dispersion system;

[0129] Further, in step S2, the oil phase solvent and the dispersant are weighed in a mass ratio of 100:3.5, added into a four-necked flask, mixed and stirred for 30 minutes at 30° C. under N2 protection to form a stable suspension dispersion system, and obtain an oil phase solution;

[0130] S3. Under the protection of nitrogen and under stirring conditions, the gelatinized starch solution and the initiator solution prepared in step S1 are slowly added to the oil phase solution prepared in step S2, and the monomer solution is added dropwise after stirring for a certain period of time. After the addition is completed, the polymerization reaction is carried out under stirring conditions for a certain period of time, and then cooled to room temperature under stirring conditions, and the mixture is allowed to stand to obtain;

[0131] Furthermore, the oil phase solvent in step S3 is n-hexadecane, and the dispersant is sodium dodecyl sulfate;

[0132] Furthermore, in step S3, the volume ratio of the oil phase solution to the water phase solution is 4.5:1, the polymerization temperature is 75° C., the stirring speed during the polymerization is 500 r / min, the polymerization time is 2.5 h, and the standing time is 5 min;

[0133] S4. The bottom white emulsion in the mixture obtained in step S3 is centrifuged to obtain a high-purity emulsion;

[0134] S5. The high-purity emulsion obtained in step S4 is slowly poured into anhydrous ethanol stirred at high speed, washed several times, and then dried in a vacuum drying oven to obtain a spherical starch-based cement-based material curing agent;

[0135] Furthermore, in step S5, the ethanol washing times are 3 times, and the drying condition in a vacuum drying oven is 45° C. for 24 hours;

[0136] S6. Take a SEM photo of the spherical starch-based cement-based material internal curing agent obtained in step S5, and use an image processing method to calculate the particle sphericity of the obtained SEM photo. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, the sphericity is a spherical starch-based cement-based material internal curing agent.

[0137] Furthermore, the specific implementation method of step S6 includes the following steps:

[0138] S6.1. Take a SEM photograph of a spherical starch-based cement-based material curing agent obtained in step S5;

[0139] S6.2. Process the SEM photograph obtained in step S6.1 into a binary image, extract the projected area of ​​the particles of the spherical starch-based cement-based material curing agent and the diameter of the minimum circumscribed circle of the particles;

[0140] S6.3. Set the sphericity s to the ratio of the diameter D of the circle with equal projected area of ​​the particle to the diameter Dc of the smallest circumscribed circle of the particle. The sphericity value range is 0-1. The closer s is to 1, the closer the shape of the particle is to a sphere. The calculation expression is:

[0141]

[0142]

[0143] Where S is the projected area of ​​the particle;

[0144] S6.4. Compare the sphericity s obtained in step S6.3. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, a spherical starch-based cement-based material internal curing agent is obtained.

[0145] The method for synthesizing a spherical starch-based cement-based material internal curing agent described in this embodiment, the SEM photo of the synthesized spherical starch-based cement-based material internal curing agent is as follows Fig. 9 As shown, it can be seen that the particle size distribution of SSSP particles is uniform and the particle surface is smooth.

[0146] The method for synthesizing a spherical starch-based cement-based material internal curing agent described in this embodiment, after the synthesized spherical starch-based cement-based material internal curing agent is stirred and dried in ethanol, the SSSP particles can be well dispersed, indicating that the binding force between the particles is not strong. The water-absorbed SSSP particles are placed in an evaporating dish, such as Fig.10 As shown, we can see good spherical gel particles. Generally speaking, observing whether the SAP particles synthesized by reverse suspension are spherical often requires observation under a scanning electron microscope, which is time-consuming and expensive. The morphology of the direct water-absorbed gel is simple and efficient, which provides a way to judge the morphology of SAP. Specific implementation method four:

[0148] A method for synthesizing a spherical starch-based cement-based material internal curing agent comprises the following steps:

[0149] S1. configuring an aqueous solution, including a gelatinized starch solution, an initiator solution and a monomer solution;

[0150] Furthermore, the specific implementation method of step S1 includes the following steps:

[0151] S1.1. Prepare gelatinized starch solution: weigh starch and deionized water in a mass ratio of 1:20, then place the starch in a three-necked flask, add deionized water, and gelatinize for 0.5-1.5h at a stirring rate of 200r / min in a water bath at 85℃ under nitrogen protection to obtain a gelatinized starch solution;

[0152] S1.2. According to the weighed starch mass in step S1.1, the hydrophilic monomer, initiator, and cross-linking agent are weighed respectively. The mass ratio of starch to hydrophilic monomer is 1:5, the initiator is 1wt% of the mass of the hydrophilic monomer, and the cross-linking agent is 0.1wt% of the mass of the hydrophilic monomer;

[0153] S1.3. Prepare initiator solution: weigh initiator and deionized water in a mass ratio of 1:5, stir evenly under nitrogen protection to obtain an initiator solution;

[0154] S1.4. Prepare a monomer solution: weigh a hydrophilic monomer and deionized water in a mass ratio of 1:5, stir evenly under nitrogen protection, adjust the pH value with sodium hydroxide, then add a crosslinking agent, stir evenly, and obtain a monomer solution;

[0155] Furthermore, in step S1, the starch is one of cassava starch and corn starch, the hydrophilic monomer is an amide compound carrying an amide group and a sulfonic acid compound carrying a sulfonic acid group, the initiator is a composition of sodium persulfate and mercaptosuccinate in a mass ratio of 1:4, and the crosslinking agent is divinylphenol;

[0156] Further, the amide compound carrying an amide group is dimethyl acrylamide, and the sulfonic acid compound carrying a sulfonic acid group is sulfonic acrylate;

[0157] S2. Under the protection of nitrogen, an oil phase solution is prepared to form a suspended dispersion system;

[0158] Furthermore, in step S2, the oil phase solvent and the dispersant are weighed in a mass ratio of 100:4, added into a four-necked flask, mixed and stirred for 30 minutes at 30° C. under N2 protection to form a stable suspension dispersion system, and obtain an oil phase solution;

[0159] S3. Under the protection of nitrogen and under stirring conditions, the gelatinized starch solution and the initiator solution prepared in step S1 are slowly added to the oil phase solution prepared in step S2, and the monomer solution is added dropwise after stirring for a certain period of time. After the addition is completed, the polymerization reaction is carried out under stirring conditions for a certain period of time, and then cooled to room temperature under stirring conditions, and the mixture is allowed to stand to obtain;

[0160] Furthermore, the oil phase solvent in step S3 is n-heptane, and the dispersant is a composition of Span-80, Tween-80 and sodium dodecyl sulfate in a mass ratio of 1:3:5;

[0161] Furthermore, in step S3, the volume ratio of the oil phase solution to the water phase solution is 4:1, the polymerization temperature is 80° C., the stirring speed during the polymerization is 450 r / min, the polymerization time is 3 h, and the standing time is 5 min;

[0162] S4. The bottom white emulsion in the mixture obtained in step S3 is centrifuged to obtain a high-purity emulsion;

[0163] S5. The high-purity emulsion obtained in step S4 is slowly poured into anhydrous ethanol stirred at high speed, washed several times, and then dried in a vacuum drying oven to obtain a spherical starch-based cement-based material curing agent;

[0164] Furthermore, in step S5, the ethanol washing times are 3 times, and the drying condition in a vacuum drying oven is 45° C. for 24 hours;

[0165] S6. Take a SEM photo of the spherical starch-based cement-based material internal curing agent obtained in step S5, and use an image processing method to calculate the particle sphericity of the obtained SEM photo. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, the sphericity is a spherical starch-based cement-based material internal curing agent.

[0166] Furthermore, the specific implementation method of step S6 includes the following steps:

[0167] S6.1. Take a SEM photograph of a spherical starch-based cement-based material curing agent obtained in step S5;

[0168] S6.2. Process the SEM photograph obtained in step S6.1 into a binary image, extract the projected area of ​​the particles of the spherical starch-based cement-based material curing agent and the diameter of the minimum circumscribed circle of the particles;

[0169] S6.3. Set the sphericity s to the ratio of the diameter D of the circle with equal projected area of ​​the particle to the diameter Dc of the smallest circumscribed circle of the particle. The sphericity value range is 0-1. The closer s is to 1, the closer the shape of the particle is to a sphere. The calculation expression is:

[0170]

[0171]

[0172] Where S is the projected area of ​​the particle;

[0173] S6.4. Compare the sphericity s obtained in step S6.3. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, a spherical starch-based cement-based material internal curing agent is obtained.

[0174] The method for synthesizing a spherical starch-based cement-based material curing agent described in this embodiment, after being stirred and dried in ethanol, the synthesized spherical starch-based cement-based material curing agent can be well dispersed, indicating that the binding force between the particles is not strong. The water-absorbed SSSP particles are placed in an evaporating dish, such as Fig.11 As shown, we can see good spherical gel particles. Generally speaking, observing whether the SAP particles synthesized by reverse suspension are spherical often requires observation under a scanning electron microscope, which is time-consuming and expensive. The morphology of the direct water-absorbed gel is simple and efficient, which provides a way to judge the morphology of SAP.

[0175] The method for synthesizing a spherical starch-based cement-based material internal curing agent described in this embodiment, the effect of the synthesized spherical starch-based cement-based material internal curing agent on the self-shrinkage of cement paste is as follows Fig.12 As shown in the figure, the water-cement ratio of the cement paste is 0.25, and the control group refers to the cement paste without SAP. The shrinkage of the cement paste usually occurs within the first week of cement hardening. Fig.12 As shown in the figure, the shrinkage of the two pastes reached a stable state in 24 hours, and SSSP had the best mitigation effect. SSSP slowed down the development of autogenous shrinkage during cement hydration by releasing water. The higher the water absorption and water retention rate of SSSP, the easier it is to evenly disperse the spherical gel formed, effectively filling the voids of cement paste, slowing down the cement hydration reaction, and having a better effect on slowing down the autogenous shrinkage of cement paste with low water-binder ratio.

[0176] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0177] Although the present application has been described above with reference to specific embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, as long as there is no structural conflict, the various features in the specific embodiments disclosed in the present application may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for synthesizing a spherical starch-based cement-based material internal curing agent, characterized in that: The steps include: S1. configuring an aqueous solution, including a gelatinized starch solution, an initiator solution and a hydrophilic monomer solution; The mass ratio of starch to hydrophilic monomer is 1:4.5-1:6, the initiator is 1wt%-1.5wt% of the mass of the hydrophilic monomer, and the crosslinker is 0.08wt%-0.12wt% of the mass of the hydrophilic monomer; the hydrophilic monomer is an amide compound carrying an amide group and a sulfonic acid compound carrying a sulfonic acid group, and the crosslinker is divinylphenol; The amide compound carrying an amide group is one or a combination of methacrylamide and dimethylacrylamide, and the sulfonic acid compound carrying a sulfonic acid group is one or a combination of sulfonic methacrylate and sulfonic acrylate; S2. Under the protection of nitrogen, an oil phase solution is prepared to form a suspended dispersion system; S3. Under the protection of nitrogen and under stirring conditions, the gelatinized starch solution and the initiator solution prepared in step S1 are slowly added to the oil phase solution prepared in step S2, and after stirring for a certain period of time, the hydrophilic monomer solution is added dropwise, and after the dropwise addition is completed, a polymerization reaction is carried out under stirring conditions for a certain period of time, and then cooled to room temperature under stirring conditions, and a mixture is obtained after standing; the volume ratio of the oil phase solution to the aqueous phase solution is 2.5:1-4.5:1; S4. The bottom white emulsion in the mixture obtained in step S3 is centrifuged to obtain a high-purity emulsion; S5. The high-purity emulsion obtained in step S4 is slowly poured into anhydrous ethanol with high-speed stirring, washed several times, and dried in a vacuum drying oven to obtain a spherical starch-based cement-based material curing agent; S6. Take a SEM photo of the spherical starch-based cement-based material internal curing agent obtained in step S5, and use an image processing method to calculate the particle sphericity of the obtained SEM photo. For particles with a sphericity lower than 0.9, adjust the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent. For particles with a sphericity greater than or equal to 0.9, the particles are regarded as a spherical starch-based cement-based material internal curing agent; Set Sphericity s The diameter of the circle that is equal to the projected area of ​​the particle D The diameter of the smallest circumscribed circle of the particle Dc The sphericity ranges from 0 to 1. s The closer it is to 1, the closer the shape of the particle is to a sphere. The calculation expression is: ; ; in, S is the projected area of ​​the particle.

2. The method for synthesizing a spherical starch-based cement-based material internal curing agent according to claim 1, characterized in that: The specific implementation method of step S1 includes the following steps: S1.

1. Prepare a gelatinized starch solution: weigh starch and deionized water in a mass ratio of 1:15-1:20, then place the starch in a three-necked flask, add deionized water, and gelatinize for 0.5-1.5 h in a water bath at 85°C-90°C and a stirring rate of 200 r / min-250 r / min under nitrogen protection to obtain a gelatinized starch solution; S1.

2. Weigh the hydrophilic monomer, initiator, and cross-linking agent according to the mass of starch weighed in step S1.1; S1.

3. Prepare an initiator solution: weigh an initiator and deionized water in a mass ratio of 1:5-1:10, stir evenly under nitrogen to obtain an initiator solution; S1.

4. Prepare a hydrophilic monomer solution: weigh a hydrophilic monomer and deionized water in a mass ratio of 1:5-1:10, stir evenly under nitrogen protection, adjust the pH value with sodium hydroxide, then add a cross-linking agent, stir evenly, and obtain a hydrophilic monomer solution.

3. The method for synthesizing a spherical starch-based cement-based material internal curing agent according to claim 2, characterized in that: In step S1, the starch is one of cassava starch and corn starch, and the initiator is sodium persulfate.

4. The method for synthesizing a spherical starch-based cement-based material internal curing agent according to claim 3, characterized in that: Step S2: weigh the oil phase solvent and the dispersant according to a mass ratio of 100:3.5-100:5.5, add them into a four-necked flask, mix and stir for 30 minutes at 25° C.-30° C. under N2 protection to form a stable suspension dispersion system to obtain an oil phase solution.

5. The method for synthesizing a spherical starch-based cement-based material internal curing agent according to claim 4, characterized in that: The oil phase solvent in step S3 is one of cyclohexane, n-heptane or n-hexadecane, and the dispersant is one of Span-80, Tween-80 and sodium dodecyl sulfate or a combination thereof.

6. The method for synthesizing a spherical starch-based cement-based material internal curing agent according to claim 5, characterized in that: The polymerization reaction temperature in step S3 is 65° C.-85° C., the stirring speed during the polymerization reaction is 350 r / min-500 r / min, the polymerization reaction time is 2.5h-3h, and the standing time is 5min-10min.

7. The method for synthesizing a spherical starch-based cement-based material internal curing agent according to claim 6, characterized in that: In step S5, the ethanol washing times are 3 times, and the product is placed in a vacuum drying oven and dried at 45° C. for 24 hours.

8. The method for synthesizing a spherical starch-based cement-based material internal curing agent according to claim 7, characterized in that: The specific implementation method of step S6 includes the following steps: S6.

1. SEM photograph of a spherical starch-based cement-based material curing agent obtained in step S5; S6.

2. The SEM photograph obtained in step S6.1 is processed into a binary image, and the projection area of ​​the particles of the spherical starch-based cement-based material curing agent and the diameter of the minimum circumscribed circle of the particles are extracted; S6.

3. Comparison of sphericity s For particles with a sphericity lower than 0.9, the synthesis method of steps S1-S5 of the spherical starch-based cement-based material internal curing agent is adjusted, and particles with a sphericity greater than or equal to 0.9 are regarded as a spherical starch-based cement-based material internal curing agent.

9. A spherical starch-based cement-based material internal curing agent, which is realized based on the synthesis method of a spherical starch-based cement-based material internal curing agent according to any one of claims 1 to 8, characterized in that: Synthesized based on the reverse suspension method.

Citation Information

Patent Citations

  • Preparation method for water-preserving and salt-tolerant alkaline concrete internal curing agent

    CN102358773A

  • Super absorbent resin with lower liquid absorbing rate, and preparation method and application thereof

    CN103113508A

  • Plurality of water-absorbing polymer particles, and method for producing plurality of water-absorbing polymer particles

    JP2018053041A

  • Water-absorbing resin composition, and production method thereof

    JP2022087609A